2008
DOI: 10.1097/01.jcn.0000317459.41015.d6
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Patients' Readiness for an eHealth Management Program for Chronic Heart Failure

Abstract: Heart failure (HF) is a major public health problem in the United States. Approximately 5 million Americans are living with HF, and each year, 550,000 more are newly diagnosed. With recent, rapidly advancing technologies, many studies have examined the effects of technology-based HF management programs. Most of these studies focused on telemonitoring devices, lacking an aspect to motivate individuals to manage their own illnesses. This exploratory study was conducted to (1) examine the readiness of patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 31 publications
(27 reference statements)
1
39
0
Order By: Relevance
“…Ten articles reported on a sample or subsample with a mean age between 65 and 70 years (Bond et al, 2007(Bond et al, , 2010Kerr et al, 2010;Mewton et al, 2013;Neafsey et al, 2011;Nguyen et al, 2008Nguyen et al, , 2013Ruland et al, 2013;Westlake et al, 2007;Zou et al, 2012), 14 articles used a sample or subsample with a mean age between 70 and 75 years (Berman et al, 2013;Hill-Kayser et al, 2011;Homenko et al, 2010;McKinstry et al, 2013;Nahm et al, 2008;Shea et al, 2006Shea et al, , 2009Sheeran et al, 2011;Trief et al, 2007Trief et al, , 2009Trief et al, , 2013Weinstock et al, 2011), and one article used a sample with a mean age of 79 years (Finkelstein et al, 2011). Four articles discussed OHITs based on a single function: three of which were concerned with information provision Sheeran et al, 2011) …”
Section: Study Characteristicsmentioning
confidence: 98%
“…Ten articles reported on a sample or subsample with a mean age between 65 and 70 years (Bond et al, 2007(Bond et al, , 2010Kerr et al, 2010;Mewton et al, 2013;Neafsey et al, 2011;Nguyen et al, 2008Nguyen et al, , 2013Ruland et al, 2013;Westlake et al, 2007;Zou et al, 2012), 14 articles used a sample or subsample with a mean age between 70 and 75 years (Berman et al, 2013;Hill-Kayser et al, 2011;Homenko et al, 2010;McKinstry et al, 2013;Nahm et al, 2008;Shea et al, 2006Shea et al, , 2009Sheeran et al, 2011;Trief et al, 2007Trief et al, , 2009Trief et al, , 2013Weinstock et al, 2011), and one article used a sample with a mean age of 79 years (Finkelstein et al, 2011). Four articles discussed OHITs based on a single function: three of which were concerned with information provision Sheeran et al, 2011) …”
Section: Study Characteristicsmentioning
confidence: 98%
“…Behavioral change for patients is a complex process, where the patient has to relearn the way to do certain health-related activities such as food intake and physical activity (Bellamy, 2004). Patients obtain information about their illness from different sources (Salo et al, 2004), and with the growing availability of new technologies, access to care has increased (Nahm et al, 2008). However, the mere knowledge or access to health-related information does not bring changes in healthrelated behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Another study showed that persons with coronary artery disease reported an increased confidence in their choice of treatment after viewing an interactive educational video online [20]. Other benefits of OPE, as perceived in literature included improved patient awareness toward the disease, reduced hospitalization, and easy access to educational material [1].…”
Section: Benefits Of Online Patient Educationmentioning
confidence: 99%
“…(32) I would feel more secure if an OPE displayed information about accreditation by a health organization. (33) I feel more confident if an OPE site does not display marketing or advertising material.…”
Section: Appendixmentioning
confidence: 99%
See 1 more Smart Citation